Sensitivity analysis of fluorescent nuclear track detectors for fast and high-energy mono-energetic neutron dosimetry - Schmidt, Stefan; Christensen, Jeppe B.; Lutz, Benjamin; Stabilini, Alberto; Yukihara, Eduardo G.; Vedelago, José (Medical physics, 2025)
Background In ion beam radiotherapy, treatment radiation fields are inevitably contaminated with secondary neutrons. The energies of these neutrons can reach several hundreds of MeV. Fluorescent nuclear track detectors (FNTDs) offer a promising solution for dosimetry of fast and high-energy neutrons, particularly given their low linear energy transfer in water (LET) detection threshold. Purpose This study presents an experimental FNTD sensitivity analysis in six fast mono-energetic neutron fields, comparing the response to poly allyl diglycol carbonate (PADC) neutron detectors, and investigates the feasibility of estimating ambient dose equivalent for neutrons, \H^*\(10). Moreover, it investigates the impact of converter thickness on the detector signal for both fast and high-energy neutrons and analyzes the resulting differences in signal. Methods FNTDs and PADCs were exposed to mono-energetic neutron fields with energies of 1.2 MeV, 2.5 MeV, 5 MeV, 6.5 MeV, 14.8 MeV, and 19 MeV and evaluated based on the track density. The \H^*\(10) values for FNTDs were determined by applying energy calibration factors, \k(E)\, which were determined through Monte Carlo (MC) simulations. The benchmarked MC model is employed to investigate the sensitivity of FNTDs to high-energy neutrons up to 200 MeV for various polyethylene (PE) converter thicknesses and to analyze the detector signal, including the particle type and the recoil proton LET. Results The sensitivity values revealed an energy dependence for FNTDs, with variations by a factor of up to 23, whereas PADC detectors showed a smaller variation, ranging from 3 to 12. Accurate \H^*\(10) estimation can be achieved employing MC-derived \k(E)\ factors, with deviations not exceeding \10\, %\. The sensitivity values increased almost continuously up to \200 \,\mathrmMeV\ for PE converter thicknesses above \2 \,\mathrmmm\, whereas plateaued for thinner PE converters above 10 MeV to 15 MeV. For neutrons above \20 \,\mathrmMeV\, the generated fragments are deuterons, tritons and ^4\rm He\, which constitutes up to \15 \,%\ or more of the total fluence in a \150 \,\mathrmMeV\ neutron field. The recoil proton LET dropped from approximately \47\, \mathrmkeV\,\umu\mathrmm^-1\ to nearly one order of magnitude less between 1.2 MeV and 19 MeV, with an average LET of approximately \2\, \mathrmkeV\,\umu\mathrmm^-1\ at \150 \,\mathrmMeV\. Conclusions This study compares FNTD and PADC detector sensitivities, demonstrating a notable energy and converter thickness dependence for FNTDs, which is essential for precise dosimetry. Accurate \H^*\(10) values for fast mono-energetic neutrons up to \19 \,\mathrmMeV\ were determined utilizing MC simulations. A benchmarked MC model for fast neutrons was then applied to analyze the FNTD signal for high-energy neutrons.
Zuerst veröffentlicht: 20. April 2025
Gesehen am 02.10.2025